Caffeine Therapy for Apnea of Prematurity: Role of the Circadian CLOCK Gene Polymorphism - Guo, Hong-Li; Long, Jia-Yi; Hu, Ya-Hui; Liu, Yun; He, Xin; Li, Ling; Xia, Ying; Ding, Xuan-Sheng; Chen, Feng; Xu, Jing; Cheng, Rui (Frontiers in Pharmacology, 2022)
Standard-dose caffeine citrate has been routinely prescribed for apnea of prematurity (AOP) management, however, some preterm infants respond well to the therapy, but others do not. The AOP phenotype has been attributed solely to immature control of respiratory system consequent to preterm birth but there also be important genetic influences. Based on our previous report, herein, we tested the hypothesis that the human Circadian Locomotor Output Cycles Kaput (CLOCK) gene polymorphisms would be involved in the response to caffeine citrate therapy in preterm infants. We also studied circadian clock interactions with aryl hydrocarbon receptor (AHR) signaling pathways in these preterm babies who received caffeine citrate. This single-center study collected data from 112 preterm infants (< 35 weeks’ gestational age) between July 2017 and July 2018 including apnea-free (n=48) and apneic (n=64) groups. Eighty-eight candidate single-nucleotide polymorphisms (SNPs) were tested by a MassARRAY system. The association analysis was estimated by using the PLINK Whole genome data analysis Toolset and SNPStats software. Linkage disequilibrium (LD) and haplotype analysis were evaluated using the Hapview software. No significant intergroup differences in allele distributions or genotype frequencies of the genes, i.e., CYP1A2, CYP3A4, CYP3A5, CYP3A7, were found in our study preterm babies. Two more SNPs in AHR gene were found to be associated with the response to caffeine citrate therapy in our pediatric patients. Notably, in the 46 candidate SNPs in CLOCK gene, 26 SNPs were found to be associated with the response to caffeine treatment in these babies. Interestingly, the significant association still retained for 18 SNPs in CLOCK gene after false discovery rate correction. Moreover, strong LD formed respectively in those variants in AHR, ADORA2A, and CLOCK genes was confirmed to be associated significantly with better response to standard-dose caffeine therapy. In summary, the CLOCK gene polymorphisms are involved in the response to caffeine therapy for neonates with AOP. Whether the AHR- and CLOCK- signaling pathways interact with each other in the caffeine treatment remains largely unclear. Future clinical studies by recruiting more immature babies and basic research are needed to explore how circadian rhythm affects the response to caffeine therapy.